Case Report: A neoantigen-targeting peptide vaccine combined with checkpoint inhibition induces tumor regression and long-term remission in a pediatric patient with metastatic hepatocellular carcinoma - Amorelli, Germano; Rabsteyn, Armin; Maier, Claus-Philipp; Trautner, Finn; Holzer, Ursula; Schäfer, Jürgen Frank; Ebinger, Martin; Handgretinger, Rupert; Nahnsen, Sven; Rammensee, Hans-Georg; Lang, Peter (Frontiers in Immunology, 2025)
Pediatric hepatocellular carcinoma (HCC) is a rare and aggressive malignancy with limited treatment options and poor prognosis, highlighting the need for innovative therapeutic strategies. Neoantigen-targeting peptide vaccination is a promising treatment approach with potential for combination therapy with checkpoint inhibition (CPI). Here, we present a case study of a pediatric patient with metastatic HCC treated with a neoantigen-derived peptide vaccine combined with CPI therapy after disease recurrence. Immunomonitoring revealed robust vaccine-induced T-cell responses, further enhanced by CPI. T-cell cloning and T-cell receptor (TCR) sequencing confirmed neoepitope specificity and clonality of the vaccine-induced T-cell response. Following immunotherapy, the inoperable metastasis regressed completely, with no further intervention. A subsequent metastasis was surgically resected, and the patient has remained in complete remission since, with an overall survival (OS) of 13 years. These findings underscore the potential of personalized peptide vaccination and demonstrate the feasibility and efficacy of combinatorial strategies in optimizing therapeutic outcome in pediatric HCC. Importantly, this case illustrates a uniquely durable remission in pediatric metastatic HCC, exceeding survival outcomes reported in previous vaccine or CPI monotherapy studies.